Elizabeth Mary Parrish at Georgia State Womans College Scrapbook, c.1925 - Parrish, Elizabeth Mary (My University)
This item is a collection of Photos from Elizabeth Mary Parrish scrapbooks. These scrapbooks include photos in and around Berrien County, as well as the Georgia State Womans College around 1925.
This item contains 77 pages in addition to 43 JPG files and 65 Photographs
Keywords: Berrien County (Ga.); Berrien County Historical Foundation (Nashville; Ga.); Grady County (Ga.)--History; Nashville (Ga.); Scrapbooks; Lowndes County (Ga.); Valdosta (Ga.); Photographs; Berrien County (Ga.)--History--Sources; Georgia State Womans College